Humanitarian Accountability in Displacement Contexts: Five Years on from the Grand Bargain. (23rd October 2021) - Martin, Diana; Singer, Sarah; Mathias, Bethan
Abstract: Humanitarian accountability has been the subject of increased attention in recent years. However, examination of how its principles and practices play out in displacement contexts is an under-explored area. In this Editorial, we outline the development of humanitarian accountability standards and practice, with particular focus on their applicability to displacement contexts. As we refer to and introduce the papers of this special issue, we reflect on positive developments and the challenges remaining. It is a particularly prescient time to reflect on the 'state of play' of accountability in this sector, given it is five years since the adoption of the Grand Bargain and the "Participation Revolution", through which stakeholders undertook to increase the relevance and efficiency of humanitarian response by giving prominence to affected populations' participation in decisions which affect their lives. Despite these commitments, however, true progress is hampered by entrenched power imbalances. In the pyramid of power relations which denote the power to influence programming, displaced populations remain at the bottom, often unheard and silenced. Yet, only when displaced communities are able to influence the kind of aid they receive, can humanitarian responses truly address their needs and pave the way for more secure, protected and resilient communities.